VARIABILITY IN GROWTH CHARACTERS AND ANTI-NUTRITIONAL PROPERTIES OF SICKLE POD (Senna obtusifolia L.) - Abubakar, A. S.; Hamza, A. M.; Tadda, S. A.; Lado, A. (FUDMA JOURNAL OF SCIENCES, 2023)
Variability in growth characters of crop species is critical in crop science; it forms the basis for breeding to improve yield, quality, and adaptation of crops to local climatic and soil conditions. Not much has been reported on the diversity of Senna obtusifolia L. in this agro-ecological zone. The study was carried out to assess the variability in growth characters and anti-nutritional factors in different accessions of Senna obtusifolia. Field and laboratory experiments were conducted at the Teaching and Research Farm of Department of Agronomy and Laboratory of Biochemistry Department, Bayero University, Kano (BUK) in the Sudan savannah Zone of Nigeria (latitude 110 58’N, longitude 8025’ and 45 m above sea level). Four accessions of Senna obtusifolia were used as the treatments and laid out in a Randomized Complete Block Design (RCBD), in three replicates. The result revealed significant differences (p<0.05) in number of pods per plant across the accessions, where accession 1 and 4 recorded the highest number of pods (250.33) and (175.20) respectively. The same trend was observed in number of branches per plant in accession 1 and 4 (15.47 and 9.73, respectively). The result of the anti-nutritional factors analysis revealed the presence of tannins, saponins, alkaloids, phenols, steroids, quinines and terpenoides in the seeds and leaves of Senna obtusifolia. Growth characters and anti nutritional properties of sickle pod varies with accessions evaluated, this therefore provides baseline information that could be used for breeding purposes in harnessing the huge potential benefits of Senna obtusifolia.